2009
DOI: 10.1167/9.2.18
|View full text |Cite
|
Sign up to set email alerts
|

Learning cue validity through performance feedback

Abstract: Targets of a visual search are often not randomly positioned within a scene, but may be more likely to co-occur adjacent to other objects or background properties. Studies on target-cue co-occurrence (e.g. cue validity) suggest that observers can exploit this knowledge to increase performance in detection and localization tasks. However, little is known regarding how observers learn this co-occurrence. The present experiment sought to determine if observers were capable of learning the probability of cue valid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
34
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 103 publications
4
34
0
Order By: Relevance
“…The findings are consistent with studies showing the benefits of learning eye movement strategies on perceptual performance in visual search tasks (Chukoskie et al, 2013; Droll et al, 2009; Koehler, Akbas, Peterson, & Eckstein, 2012). Yet, the importance or role of eye movements outside the scope of visual search has not been demonstrated.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The findings are consistent with studies showing the benefits of learning eye movement strategies on perceptual performance in visual search tasks (Chukoskie et al, 2013; Droll et al, 2009; Koehler, Akbas, Peterson, & Eckstein, 2012). Yet, the importance or role of eye movements outside the scope of visual search has not been demonstrated.…”
Section: Discussionsupporting
confidence: 91%
“…Perceptual learning has been shown to change which stimulus features and spatial locations the visual system selects for task-specific processing (Ahissar & Hochstein, 1993; Dosher & Lu, 1998; Droll et al, 2009; Eckstein et al, 2004; Peterson et al, 2009). In this work, we showed that humans are able to adjust their eye movements to optimize the sampling of a novel visual stimulus, with these modulations contributing significantly to task performance maximization beyond the contributions of covert mechanisms alone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found a strong modulation of attentional capture, which we relate to statistical learning (e.g., Chun & Jiang, 1998;Droll, Abbey, & Eckstein, 2009;Fiser & Aslin, 2001, 2002Rosenthal, Fusi, & Hochstein, 2001;Saffran, Aslin, & Newport, 1996;Saffran, Newport, Aslin, Tunick, & Barrueco, 1997;Turk-Brown, Jungé, & Scholl, 2005). The higher the rate of the onset distractors, the stronger they were suppressed.…”
Section: Introductionmentioning
confidence: 84%
“…In 20% of randomly interleaved so-226 called catch trials none of the four possible target X stimuli dimmed 227 and the trial ended after 3.5 s. These catch trials were discarded from 228 all further analysis. The task also included a hidden schedule of proba-229 bilities changing rapidly every 25 correct trials (probability that a 230 dimming event was linked to a specific color, see Droll et al, 2009 Fig. 1.…”
mentioning
confidence: 99%